1983
DOI: 10.1161/01.hyp.5.5_pt_2.iii132
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an angiotensin converting-enzyme inhibitor on diuretic-induced metabolic effects in hypertension.

Abstract: SUMMARY Diuretic therapy is frequently accompanied by undesirable biochemical changes and side-effects. Two multicenter trials compared the effects of captopril combined with a diuretic to the administration of either agent alone in mild-to-moderate hypertensives. In addition to blood pressure, effects on serum potassium, uric acid, glucose, and cholesterol were examined. The first study (Study A) was conducted on 210 such patients randomly assigned to receive: 1) hydrochlorothiazide (H) 15 mg three times dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(39 citation statements)
references
References 13 publications
4
33
1
1
Order By: Relevance
“…The results of this multicentre trial of mild to moderate essential hypertension show that the fixed combination of C 50/HCTZ 25 once daily provided an antihypertensive effect equal in magnitude to that of the fixed combination of C 25/HCTZ 12.5 twice daily in patients already controlled by the co-administration of C 25 mg and HCTZ 12.5 mg twice daily. Moreover this study confirms previous reports (Weinberger, 1982(Weinberger, , 1983(Weinberger, , 1985 demonstrating the additive effect of the two agents on blood pressure. Indeed, beneficial blood pressure response (normalized blood pressure or decreased by 10% or more) was seen in 88% of the patients as reported by Clementy et al (1988).…”
Section: Discussionsupporting
confidence: 92%
“…The results of this multicentre trial of mild to moderate essential hypertension show that the fixed combination of C 50/HCTZ 25 once daily provided an antihypertensive effect equal in magnitude to that of the fixed combination of C 25/HCTZ 12.5 twice daily in patients already controlled by the co-administration of C 25 mg and HCTZ 12.5 mg twice daily. Moreover this study confirms previous reports (Weinberger, 1982(Weinberger, , 1983(Weinberger, , 1985 demonstrating the additive effect of the two agents on blood pressure. Indeed, beneficial blood pressure response (normalized blood pressure or decreased by 10% or more) was seen in 88% of the patients as reported by Clementy et al (1988).…”
Section: Discussionsupporting
confidence: 92%
“…8,22,23 Accordingly, previous studies have shown that the addition of ACE inhibitors to thiazides can blunt or even prevent the metabolic consequences of diuretic therapy, while they enhance their antihypertensive effect. [6][7][8][9][10][11] Nonetheless, there seem to be a few studies concerning the metabolic consequences of added thiazide diuretics to ACE inhibitors. Additionally, comparison of the observed biochemical derangements between hydrochlorothiazide and indapamide when added to ACE inhibitors is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…26 Furthermore, the ACE inhibitor dosage could have also played a role in its influence in the carbohydrate tolerance, since in one study the administration of only high doses of captopril (Ͼ100 mg/day) mitigated the hyperglycaemic effect of hydrochlorothiazide. 6 Therefore, a placebo-controlled study to address the effect of ACE inhibition on sensitivity to insulin in essential hypertension needs to be carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative, hypokalemia can be minimized if ACE inhibitors or angiotensin II receptor blockers are added to the regimen. 27 …”
Section: How Clinical Pharmacists Can Help Reduce Thiazide-induced Hymentioning
confidence: 99%